2006
DOI: 10.1002/asna.200610565
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic fields in the Southern Galactic Plane Survey

Abstract: The Southern Galactic Plane Survey (SGPS) is a 1.4 GHz radio polarization and HI survey in a large part of the inner Galactic plane at a resolution of about an arcmin. Depolarization and Faraday rotation of polarized radiation from diffuse Galactic synchrotron emission, pulsars, and extragalactic sources can be used to infer information about the strength and structure of the Galactic magnetic field. Here, we discuss science results of the polarization data from the SGPS. We show from statistical analysis of r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…RM data from pulsars and polarized extragalactic point sources in the SGPS, combined with other available point source data, are being used to construct a model of the large-scale Galactic magnetic field ( Haverkorn et al 2006b;Brown et al 2006), discussing the strength of the regular magnetic field and the abundance and locations of magnetic field reversals.…”
Section: Science With the Sgpsmentioning
confidence: 99%
“…RM data from pulsars and polarized extragalactic point sources in the SGPS, combined with other available point source data, are being used to construct a model of the large-scale Galactic magnetic field ( Haverkorn et al 2006b;Brown et al 2006), discussing the strength of the regular magnetic field and the abundance and locations of magnetic field reversals.…”
Section: Science With the Sgpsmentioning
confidence: 99%
“…Further indication that the structure of the local Galactic magnetic field is rather complicated on pc and sub-pc scales comes from RM maps obtained from the diffuse Galactic synchrotron on which many reversals on small scales observed around 330 MHz with the WSRT (Haverkorn et al 2003a(Haverkorn et al , 2003b. Major progress can be expected from the new 1.4 GHz International Galactic Plane Survey observed at the DRAO and ATCA telescopes (Brown & Taylor 2001, Haverkorn et al 2006). It will provide high-resolution RM data of the diffuse emission and several 100 RM values of polarized background sources.…”
Section: Magnetic Field Reversals In the Milky Waymentioning
confidence: 99%
“…As an example of using the RM structure function to determine the outer scale of fluid turbulence, Haverkorn et al (2006a) found a zero gradient with an outer scale on the order of ∼ 10 pc for the inner Galactic Plane, indicating that the main source of turbulence had to be injected on a scale of ∼ 10 pc, which they attributed to H regions.…”
Section: Magneto-ionic Turbulencementioning
confidence: 99%